Identification of Factors And Recommendations for Improving Passenger Terminal Service Performance at Banyuwangi Airport - Deden Nugroho; Wateno Oetomo; Risma Marleno (Journal of Social Science, 2025)
The performance of passenger terminal services at Banyuwangi Airport is a critical determinant of the user experience in air transportation services, directly impacting passenger satisfaction and the airport's reputation. This research aims to evaluate the quality of services provided, identify key factors influencing service performance, and propose actionable recommendations for improvement. Using the Analytical Hierarchy Process (AHP) method, the study reveals that waiting room facilities, information services, and check-in process efficiency are the most significant elements requiring attention. Additionally, while passengers express high satisfaction with basic facilities such as hygiene and toilets, areas such as the circulation space and baggage services exhibit shortcomings that hinder operational efficiency and user comfort. To address these issues, several recommendations are proposed, including redesigning the circulation area to enhance passenger flow, optimizing baggage handling processes to improve speed and reliability, and introducing additional amenities such as more seating areas, improved signage, and dedicated zones for special needs passengers. These findings offer a strategic framework for Banyuwangi Airport managers to prioritize and implement targeted improvements, ultimately enhancing the overall passenger experience and supporting the airport's role as a gateway to East Java's tourist destinations.